Knowledge and Attitude of Mothers About Care of New Birth In The New Normal Era - Maliha Amin; Intan Kumalasari (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Background: Caring for a newborn is a challenge for parents, especially in the midst of the Covid-19 pandemic. Concerns about transmission from parents, family and medical personnel as well as limited information and delays in various activities in basic community services can lead to low quality and ability of mothers to care for babies. Objectives: This study aims to describe the knowledge and attitudes of mothers in the care of newborns in the new normal. Methods: This research is descriptive analytic research using observational method. The population in this study were mothers aged 0-28 days who live in the work area of ​​Posyandu Jayalaksana RW 03 Village 3-4 Ulu Palembang with a sample of 44 people, data collection using questionnaires for assessment variables and attitudes using a Likert scale with a range of 1- 5 which consists of favorable and unfavorable statements. Univariate data analysis to assess the characteristics and frequency distribution of variables Results: Knowledge is strongly influenced by age, education and occupation. most of the respondents have a fairly good knowledge of 61.4% and have a good attitude that is 59.1% in caring for newborns during the new normal period. Conclusion: Good knowledge causes the right attitude and behavior in the care of newborns, it takes the cooperation of parents, families and health workers so that the success of caring for babies in the new normal is more optimal.